2012
DOI: 10.1007/s12264-012-1211-0
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain

Abstract: Formaldehyde at a very low concentration up-regulates TRPV1 expression through mitogen-activated protein kinase and PI3K, but not PKC, signaling pathways. These results further support our previous finding that TRPV1 in peripheral afferents plays a role in bone cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…As in our previous studies [19,20,37], the hindpaw withdrawal threshold (PWT) was determined by a calibrated series of von Frey hairs (1,2,4,6,8,10,15, and 26 g; Stoelting, Wood Dale, IL), applied in ascending order for 3 s to the center of the plantar surface of the left hindpaw. A positive response was considered only when the hindpaw was completely lifted off the platform.…”
Section: Von-frey Test For Mechanical Allodyniamentioning
confidence: 99%
See 1 more Smart Citation
“…As in our previous studies [19,20,37], the hindpaw withdrawal threshold (PWT) was determined by a calibrated series of von Frey hairs (1,2,4,6,8,10,15, and 26 g; Stoelting, Wood Dale, IL), applied in ascending order for 3 s to the center of the plantar surface of the left hindpaw. A positive response was considered only when the hindpaw was completely lifted off the platform.…”
Section: Von-frey Test For Mechanical Allodyniamentioning
confidence: 99%
“…Various cancer cells release algogenic substances such as tumor necrosis factor, bradykinin, nerve growth factor (NGF), and formaldehyde that may sensitize primary afferent neurons or destroy peripheral nerve fibers [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Neurosci Bull December 1, 2012, 28(6): 715-722 716 We found that formaldehyde concentration is elevated in the spinal cord of rats with chronic pain [6] . Formaldehyde derived from local metastasized tumor tissues excites peripheral nociceptive neurons and thus can induce cancer pain [7] .…”
Section: Introductionmentioning
confidence: 78%
“…Ten laboratories from China and the USA have contributed 11 papers to this special issue: 5 reviews and 6 full research articles [5][6][7][8][9][10][11][12][13][14][15] . This special issue aims to cover several areas of research in pain and itch, from peripheral to central mechanisms, and also from neuronal to glial mechanisms.…”
mentioning
confidence: 99%
“…First, Dong et [9] . Second, Han and colleagues show that TRPV1 expression in DRG neurons is up-regulated after exposure to formaldehyde and in the context of bone cancer pain [10] . Third, Ding et al reveal that a TRPC channel antagonist can alleviate inflammatory pain [11] .…”
mentioning
confidence: 99%